Pancreatitis in systemic lupus erythematosus: Clinical characterization and outcome analysis in concurrent pancreatitis and lupus - Sheba Charles; Benzeeta Pinto; Vineeta Shobha (Indian Journal of Rheumatology, 2021)
Objective: Pancreatitis in systemic lupus erythematosus (SLE) continues is an often under-diagnosed entity with high morbidity and mortality. The objective of this case series is to study the demographics and outcomes of lupus pancreatitis and to compare with available medical literature. Materials and Methods: Records of SLE patients admitted in our hospital between January 2012 and May 2018, were examined retrospectively. Clinical and laboratory parameters of the patients who were diagnosed with SLE and pancreatitis were obtained and analyzed. Results: The prevalence of pancreatitis in our cohort was 1.33% with 77% female preponderance. All the patients presented within 3 years of lupus onset. Pancreatitis was often associated with other disease manifestations of SLE and the mean Systemic Lupus Erythematosus Disease Activity Index 2K score at presentation was 17.4 ± 7.82. None of the patients were positive for APLA antibodies. All our patients were treated with high-dose steroids and other immunosuppression as indicated for concomitant disease activity. Complications were seen in only one patient who eventually succumbed to the disease. Conclusions: Pancreatitis in SLE is associated with disease activity. High index of suspicion, early diagnosis, and institution of steroids and immunosuppressive therapy lead to a good outcome.